Pemanfaatan Norma Sosial dalam Tata Kelola Pariwisata Berkelanjutan: Studi Kasus Air Terjun Nyarai - Hergiansyah Hergiansyah; Jumiati Jumiati (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to identify and analyze the utilization of social capital by the local government in developing sustainable tourism in terms of norms at the Nyarai Waterfall tourist attraction, Salibutan Village, Padang Pariaman Regency. This study focuses on religious norms, morality, politeness, and legal norms that have not been fully complied with. A qualitative descriptive approach method was used in this study. Research participants were identified using a purposive sampling technique. Data were obtained through observation, interviews, and documentation, then analyzed using source triangulation techniques. The results of the study indicate that the phenomenon of the utilization of norms applied, including religious norms in tourist areas that are in accordance with Islamic law. The utilization of moral norms is seen through moral and ethical values, the utilization of politeness norms is seen in etiquette and respect, and the use of legal norms applied is adjusted to statutory regulations. The presence of the local government in the utilization of norms plays an important role in ensuring that norms and regulations are implemented. The local government, in collaboration with the Pokdarwis (Tourism Group), provides education and outreach to visitors through direct guidance and information boards available in the Nyarai Waterfall tourist area. With this method, local governments and tourism groups can minimize and avoid conflicts and increase security in tourist areas.